Question and Answers Forum

All Questions      Topic List

Trigonometry Questions

Previous in All Question      Next in All Question      

Previous in Trigonometry      Next in Trigonometry      

Question Number 17151 by Tinkutara last updated on 01/Jul/17

The solution of the equation  cos^2 θ − 2cosθ = 4sinθ − sin2θ where  θ ∈ [0, π] is

$$\mathrm{The}\:\mathrm{solution}\:\mathrm{of}\:\mathrm{the}\:\mathrm{equation} \\ $$$$\mathrm{cos}^{\mathrm{2}} \theta\:−\:\mathrm{2cos}\theta\:=\:\mathrm{4sin}\theta\:−\:\mathrm{sin2}\theta\:\mathrm{where} \\ $$$$\theta\:\in\:\left[\mathrm{0},\:\pi\right]\:\mathrm{is} \\ $$

Answered by ajfour last updated on 01/Jul/17

4sin θ−2sin θcos θ+2cos θ−cos^2 θ=0  2sin θ(2−cos θ)+cos θ(2−cos θ)=0  (2−cos θ)(2sin θ+cos θ)=0  ⇒   2sin θ+cos θ=0  or    tan θ=−(1/2)   In [0,π],  θ=π−tan^(−1) ((1/2)) .

$$\mathrm{4sin}\:\theta−\mathrm{2sin}\:\theta\mathrm{cos}\:\theta+\mathrm{2cos}\:\theta−\mathrm{cos}\:^{\mathrm{2}} \theta=\mathrm{0} \\ $$$$\mathrm{2sin}\:\theta\left(\mathrm{2}−\mathrm{cos}\:\theta\right)+\mathrm{cos}\:\theta\left(\mathrm{2}−\mathrm{cos}\:\theta\right)=\mathrm{0} \\ $$$$\left(\mathrm{2}−\mathrm{cos}\:\theta\right)\left(\mathrm{2sin}\:\theta+\mathrm{cos}\:\theta\right)=\mathrm{0} \\ $$$$\Rightarrow\:\:\:\mathrm{2sin}\:\theta+\mathrm{cos}\:\theta=\mathrm{0} \\ $$$$\mathrm{or}\:\:\:\:\mathrm{tan}\:\theta=−\frac{\mathrm{1}}{\mathrm{2}} \\ $$$$\:\mathrm{In}\:\left[\mathrm{0},\pi\right],\:\:\theta=\pi−\mathrm{tan}^{−\mathrm{1}} \left(\frac{\mathrm{1}}{\mathrm{2}}\right)\:. \\ $$

Commented by Tinkutara last updated on 01/Jul/17

Thanks Sir!

$$\mathrm{Thanks}\:\mathrm{Sir}! \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com